Association of Serum HMGB2 Levels With In-Stent Restenosis: HMGB2 Promotes Neointimal Hyperplasia in Mice With Femoral Artery Injury and Proliferation and Migration of VSMCs. Issue 4 (April 2017) - He, Yu Hu; Wang, Xiao Qun; Zhang, Jian; Liu, Zhu Hui; Pan, Wen Qi; Shen, Ying; Zhu, Zheng Bin; Wang, Ling Jie; Yan, Xiao Xiang; Yang, Ke; Zhang, Rui Yan; Shen, Wei Feng; et al.
Abstract : Objective—: In a previous study, we established diabetic and nondiabetic minipig models with coronary artery in-stent restenosis (ISR). Mass spectrometry showed that high-mobility group box (HMGB) 2 level was higher in ISR than in non-ISR tissue from diabetic minipigs. We here investigated whether serum HMGB2 levels were related to ISR in coronary artery disease patients. The effect of HMGB2 was evaluated in mice with femoral artery wire injury and in human aortic smooth muscle cells. Approach and Results—: From 2513 patients undergoing coronary artery intervention and follow-up angiography at ≈1 year, 262 patients were diagnosed with ISR, and 298 patients with no ISR were randomly included as controls. Serum HMGB2 levels were significantly higher in patients with ISR than in those without ISR and were associated with ISR severity. Multivariable logistic regression analysis showed that HMGB2 level was independently associated with ISR. In experiments, HMGB2 expression was increased in vascular tissue after injury. Perivascular HMGB2 administration promoted injury-induced neointimal hyperplasia in C57Bl/6 mice compared with in the control, whereas such pathophysiological features were attenuated in Hmgb2 –/– mice. Mechanistically, HMGB2 enhanced neointimal hyperplasia in mice and proliferation and migration in human aortic smooth muscle cells by inducing reactive oxygen species through increased p47phox phosphorylation. Knocking down p47phox, however, inhibited HMGB2-induced effects in human aortic smooth muscle cells. Finally, HMGB2-induced effects were significantly declined in receptor of advanced glycation end products knockdown or deficient cells, but not in Toll-like receptor 4 knockdown or deficient cells. Conclusions—: Serum HMGB2 levels were associated with ISR in patients. HMGB2 promoted neointimal hyperplasia in mice with arterial wire injury through reactive oxygen species activation. Abstract : Supplemental Digital Content is available in the text.